Management of Early Progressive Corneal Ectasia : Accelerated Crosslinking Principles - Mazzotta, Cosimo; Raiskup, Frederik; Baiocchi, Stefano; Scarcelli, Giuliano; Friedman, Marc D.; Traversi, Claudio (Springer International Publishing : Imprint: Springer, 2017)
This book provides a rapid overview of crosslinking protocols and the therapeutic guidelines to optimize the application according to patients age and ectasia staging. This book is unique in the field of crosslinking therapy, as it gives the readers a complete guide for their daily practice to understand the modern accelerated crosslinking protocols, indications and customized treatment strategies. Ophthalmic specialists, opticians, optometrists and doctors working in ophthalmic settings, will find this book to be a 'go-to' guide for furthering clinical knowledge of this specialized treatment for early progressive corneal ectasia.
Keywords: Medicine.; Ophthalmology.; elektronické knihy; electronic books